767 Magnetic Resonance Imaging in the Assessment of Patients with Breast Cancer Undergoing Neoadjuvant Chemotherapy: Evaluation of the Prognostic Value of Mid-Chemotherapy and Post-Chemotherapy Scans. (4th May 2021) - Davenport, M; Okhiria, R; Barrett, E; Highton, L
Abstract: Introduction: Magnetic Resonance Imaging (MRI) is used to assess the response to Neoadjuvant Chemotherapy (NAC) when used in patients with breast cancer. Method: This retrospective observational study compared patterns of tumour response at mid-chemotherapy and post-chemotherapy MRIs to histological outcomes. 118 cases of breast cancer, from a local database, were included. Results: There was a significant association between complete pathological response in resected breast tissue and complete radiological response on both mid-chemotherapy MRI (p = 0.007) and post-chemotherapy MRI (p < 0.001). In patients who had both scans, 100% of those with complete response at mid-chemotherapy scan maintained this response pattern. In those who had both scans, complete response at the mid-chemotherapy scan had a PPV for complete pathological response in resected breast tissue of 92% compared to 64% in those with complete response that was not achieved until the post-chemotherapy scan. There was a trend towards an association between early complete radiological response and complete pathological response (p = 0.124). Conclusions: Both scans have significant prognostic value. A mid-chemotherapy scan may have superior prognostic value when complete response is achieved, though larger studies are needed to determine the significance. 100% maintenance of complete radiological response after the mid-chemotherapy scan highlights the possibility that some post-chemotherapy scan could be avoided.